Penanganan Komplain untuk Meningkatkan Kepuasan Pelanggan di Restoran Stjerne Dining Brew Surabaya - Dea Devina; Ferizal Deddy Renaldy; Putri Krisma Salsabila; Wiwin Wachidyah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The purpose of this study is to analyze the handling complaint process, identify complaint resolution strategies, evaluate their impact on customer satisfaction, examine the challenges faced, and assess the role of Standard Operating Procedures (SOP) in improving the effectiveness of penanganan komplain to support service quality and customer loyalty at Stjerne Dining Brew Surabaya. This study employs a qualitative method with a direct observation approach at Stjerne Dining Brew Surabaya. Based on the results and discussion, it can be concluded that the implementation of penanganan komplain has been fairly effective through a systematic process, starting from listening to complaints, showing empathy, to follow-up actions. Flexible, prompt, and customer-oriented complaint resolution strategies are able to increase satisfaction and build customer loyalty. Positive impacts are reflected in increased trust, perceived service quality, and positive word of mouth. However, there are still challenges such as limited employee authority, team coordination, and work pressure. The role of SOP is very important in maintaining service consistency, although it needs to be supported by continuous training. Overall handling complaint becomes a strategic factor in improving